ERS International Congress 2021: highlights from the Interstitial Lung Diseases Assembly - Guler, Sabina; Cuevas-Ocaña, Sara; Nasser, Mouhamad; Wuyts, Wim A.; Wijsenbeek, Marlies S.; Froidure, Antoine; Bargagli, Elena; Renzoni, Elisabetta A.; Veltkamp, Marcel; Spagnolo, Paolo; Nunes, Hilario; McCarthy, Cormac; et al. (ERJ Open Research, 2022)
This article provides an overview of scientific highlights in the field of interstitial lung disease (ILD), presented at the virtual European Respiratory Society Congress 2021. A broad range of topics was discussed this year, ranging from translational and genetic aspects to novel innovations with the potential to improve the patient pathway. Early Career Members summarise a selection of interesting findings from different congress sessions, together with the leadership of Assembly 12 - Interstitial Lung Disease. - Tweetable abstract ERSpublications - click to tweetThis article highlights scientific advances in the field of ILD presented at #ERSCongress 2021, and provides valuable new insights into disease pathophysiology, potential therapeutic targets and disease course of different ILDs https://bit.ly/3ynCMtF